Disputas, silêncios e esvaziamentos: análise das prescrições legais para a educação das relações étnico-raciais - Santos, Vaniery Patricio Amorim dos (2024)
This dissertation investigates the secondary education prescriptions for ethnic-racial relations education in secondary education, implemented based on rulings 10.639/03 and 11.645/08, which impose the inclusion of afro-brazilian, african and indigenous history and culture classes in brazilian schools. By means of a theoretical-critical approach, this study analises state curriculum documents, their interpretations and reconfigurations at a regional level, highlighting the importance of education on ethnicracial relations to form a more equitable and egalitarian society. Through qualitative analysis of the Regional Curriculum Guidelines, specifically from the states of Amazonas and Paraíba, the gaps between federal and regional documents are discussed and, moreover, among documents from the federative units, highlighting operationalizations, depletion and erasure of concepts related to this theme. Therefore, it becomes noteworthy the necessity of a curriculum that promotes not only inclusion, but the central placement of ethnic-racial issues, defying power and privilege structures and ensuring the complexity of the mobilized concepts. The study points to the relevance of deeply knowing and understanding the curriculum documents as auxiliary resources for teachers when facing hegemonic discourses and in promoting egalitarian and transformative educational spaces and, in order to do that, emphasizes the critical role of language when building social relations and ideologies, proposing a reflection on how word choice, references and contexts are able to contribute for an education that respects and values the diversity and complexity of Brazil’s ethnic-racial composition. It’s concluded that education for ethnic-racial relations is fundamental for the construction of a citizen and that an effective application of rulings 10.639/03 and 11.645/08 requires a continuous commitment to critical analysis, the conscious implementation of curriculums and training qualified teachers to deal with the complexity of ethnic-racial relations. The dissertation highlights the need of advancements in educational policy and the necessary challenges of this field, in order to contain setbacks and ensure advancements in pedagogical practices that stand up to ethnic-racial inequalities, promoting social transformation through what the education is capable of accomplishing